2019
DOI: 10.1016/j.bbmt.2019.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Post-Transplantation Outcomes of Enteral versus Parenteral Nutrition in Pediatric Hematopoietic Stem Cell Transplantation: A Systematic Review of Randomized and Nonrandomized Studies

Abstract: Background: Hematopoietic stem cell transplantation (HSCT) involves the administration of chemotherapy followed by the infusion of donor stem cells. After treatment, children can consequently experience nausea, vomiting, diarrhea, anorexia and mucositis, which negatively impact oral intake leading to rapid deterioration in nutritional status and risk of malnutrition. Nutrition support therefore becomes necessary to circumvent these adverse effects. This has traditionally been provided via parenteral nutrition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 56 publications
(179 reference statements)
3
35
0
2
Order By: Relevance
“…On the other hand, PN patients were found have blood culture positivity to several microorganisms (e.g., Staphylococcus, Enterococcus and Streptococcus genera), mainly from day 5 to 30 post-HSCT, leading to systemic infections and clinical complications. Our results regarding the clinical outcomes of EN patients were generally in line with most of the previous studies in literature conducted on adult cohorts post-HSCT [18][19][20][21][22][23]. However, we cannot fail to mention that other studies provide conflicting results for what concern the clinical outcomes of EN assumption in HSCT adult patients [52,53].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…On the other hand, PN patients were found have blood culture positivity to several microorganisms (e.g., Staphylococcus, Enterococcus and Streptococcus genera), mainly from day 5 to 30 post-HSCT, leading to systemic infections and clinical complications. Our results regarding the clinical outcomes of EN patients were generally in line with most of the previous studies in literature conducted on adult cohorts post-HSCT [18][19][20][21][22][23]. However, we cannot fail to mention that other studies provide conflicting results for what concern the clinical outcomes of EN assumption in HSCT adult patients [52,53].…”
Section: Discussionsupporting
confidence: 89%
“…Although post-HSCT enteral feeding is being increasingly recommended [37][38][39], intravenous nutrient intake (PN) is still the first-line nutritional approach for the patients who received HSCT due to its compliance, but it has been associated with several clinical and microbiological adverse effects, including infections and GM dysbiosis [18][19][20][21][22][23][24]. So far, the central role of the GM composition and biodiversity in patients undergoing HSCT has been largely evaluated in several publications, highlighting the disruption of the gut microbial mutualistic asset after the transplant (i.e., until 30 days post-HSCT) compared to the baseline, due to all HSCT conventional treatments that can alter the GM recovery possibilities post-HSCT [4,5,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the paediatric population, the few studies comparing EN to PN involving a limited number of patients, found that EN had potential benefits regarding aGvHD and platelet engrafment [24]. Considering the increasing knowledge concerning the role of gut microbiota dysbiosis in the development of main complications after HSCT, these benefits may be potentially explained by the maintenance of gut eubyosis and epithelium integrity in patients receiving EN [25].…”
Section: Introductionmentioning
confidence: 99%
“…19,25 However, interpretations of these studies among children and adolescents with cancer are difficult because of study design limitations relating to numbers of patients, non-randomized trial designs, different diagnoses, concomitant parenteral nutrition and limitations on nutritional assessment methods. 2,24,25,[43][44][45][46][47] Furthermore, these studies did not describe the amount of tube feeding supplement intake.…”
Section: Discussionmentioning
confidence: 99%